2021
DOI: 10.3390/children8080704
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Incubators Do Not Protect from High Noise Levels in the Neonatal Intensive Care Unit and Are Relevant Noise Sources by Themselves

Abstract: Background: While meaningful sound exposure has been shown to be important for newborn development, an excess of noise can delay the proper development of the auditory cortex. Aim: The aim of this study was to assess the acoustic environment of a preterm baby in an incubator on a newborn intensive care unit (NICU). Methods: An empty but running incubator (Giraffe Omnibed, GE Healthcare) was used to evaluate the incubator frequency response with 60 measurements. In addition, a full day and night period outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Finally, a concern about incubators may be the constant noise of the fan-operated airflow. Even though the American Academy of Pediatrics recommends avoiding sound levels above 45 dB in neonatal care units, some studies demonstrated noise within incubators exceeded these recommendations frequently ( 59 , 60 ), disrupting sleep cycles ( 61 ) and possibly influencing hearing development.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a concern about incubators may be the constant noise of the fan-operated airflow. Even though the American Academy of Pediatrics recommends avoiding sound levels above 45 dB in neonatal care units, some studies demonstrated noise within incubators exceeded these recommendations frequently ( 59 , 60 ), disrupting sleep cycles ( 61 ) and possibly influencing hearing development.…”
Section: Resultsmentioning
confidence: 99%
“…Voices can also positively affect cardiorespiratory stability [29] and feeding and growth factors [30], and they have been found to reduce infant pain thresholds [31]. Yet, despite being so important, voices might even be excluded by the incubator [27,28]; however, this allows the penetration of a higher-than-desirable level of mechanical noises from medical machines [32]. Parent-child interaction can also be drastically impoverished in that caregivers might not have the opportunity to notice and respond to the infant's cues while also being impeded by the medical equipment surrounding them or the clinical state of the infant, which may prevent them from exercising their ability to provide the quality and quantity of experiences that a full-term infant might benefit from.…”
Section: Introductionmentioning
confidence: 99%
“…A baby incubator is a medical device that is used to optimize humidity and temperature within normal limits and is helpful in minimizing the risk of direct contact with other people and the environment that has the potential to transmit the disease because the baby's organ functions are still not good. The incubator is one of the medical supports commonly used in the emergency room or neonate intensive care unit (NICU) [2]. In general, the working principle of a baby incubator is to  ISSN: 2252-8938 Int J Artif Intell, Vol.…”
Section: Introductionmentioning
confidence: 99%